(untitled) (Discourse of Law and Administration, 2021)
The main subject of research presented in this study is determining the law applicable to non-contractual obligations resulting from coronavirus infection of a employees who perform cross-border work. In this context, firstly it was crucial to create a concept of a cross-border employment relationship, i.e. an employment relationship that is connected to the territory of more than one country. Subsequently, it came to the choice of legal act, applied in order to determine the law applicable to the non-contractual obligations arising from the tort committed by an employer against an employee. Among the countries that are members of European Union this liability is regulated by the Regulation (EC) No 864/2007 of the European Parliament and of the Council of 11 July 2007 on the law applicable to non-contractual obligations (Rome II), specifically Article 4 thereof, which contains the general rule of cross-border liability concerning tort/delict, as the EU legislator did not provide for specific regulation of tortious liability resulting from the employment relationships. Pursuant to the aforementioned provision, the law applicable to obligations arising from the commission of a tort by an employer against an employee is the law of the place where the damage occurs. Article also indicates the legal norms, the violation of which will most often determine the employer’s liability for committing a tort towards an employee, (health and safety rules).